The Vermicidal Effectivity of Wudani Leaf Extract (Quisqualis indica Linn) in Treating Infection caused by Gastrointestinal Worms in Cattle - Ida Bagus Komang Ardana; Made Suma Anthara; Dan Anak Agung Gde Oka Dharmayudha; DK Harya Putra (Journal of Global Pharma Technology, 2017)
The present study was aimed to study whether application of 100% extract of wudani leaf (Quisqualis indica Linn) was able to kill gastrointestinal worms Strongylus Sp. (vermicidal effect). In order to make comparation with commercial drug commonly used, one group was treated with Rheindazol (100 ml of Rheindazol contain 10 gram of albendazol) at a single dose of 10 mg/kg of body weight (BW). The other 3 groups were subjected to a single treatment with 100% wudani leaf extract at 10 mg, 15 mg, and 20 mg/kg of BW, respectively. Assessment on its vermicidal effect was carried out by conducting fecal egg count reduction (FECR). The results showed that the vermicidal property of 100% wudani leaf extract given at 10mg/kg BW was 100% and this was significantly (P < 0.01) higher than that of dose of 15 kg/kg BW (92.4%), 20 mg/kg BW (96%) and even compared to that of albendazol treatment (96%). Thus, from the present in vivo study, it can be concluded that 100% wudani leaf extract due to its vermicidal property can be effectively used to cure gastrointestinal worm infection and, therefore, can be subsequently applied to overcome worm infection in cattle. Keywords: Gastrointestinal worm, Wudani leaf extract, Vermicidal property.